Digest book of the 7th Symposium on Applied Electromagnetics, SAEM’18, Podčetrtek, Slovenia, June 17 - June 20, 2018 (University of Maribor Press, 2018)
On behalf of the International Scientific Committee and the Organising Committee we are very pleased to welcome all participants of the 7th Symposium on Applied Electromagnetics – SAEM’2018, which will be held from 17th to 20th June, 2018, in Podčetrtek, Slovenia. Podčetrtek is a settlement and a municipality in eastern Slovenia. The area traditionally belonged to the region of Styria. The castle in Podčetrtek was mentioned in written sources in 1209 as de Landesperc. The name appears on a 1763–87 map in both German and Slovene as Landsberg Windisch Pod Tschetertkom. The name implies that the castle above the settlement was once called *Četrtek (literally, ’Thursday’). The motivation for the name is unknown. It may refer to the day that court sentences were handed down, to a market day, to a day of corvée, or to the day when the settlement was founded. In the past, the German name of the settlement was Windisch Landsberg. SAEM’2018 is aimed at the presentation of research work results and/or the survey of works in various areas of Applied Electromagnetics and Power&Energy. The Symposium is devoted to exchanging ideas, presenting achievements and results, providing the forum for researchers and academics. Open and friendly atmosphere, which our conferences are known for, encourages especially young researchers to present their achievements and ideas, even in an early stage of their research work. The venue also gives many opportunities for establishing professional links and discussing collaboration areas for further international research projects and cooperation. We would like to ensure you that the organizers will do their best to create and maintain a friendly and warm atmosphere at the conference, both in scientific and social programme. Thank you for your coming to Slovenia. We wish you a lot of fruitful scientific debates during the Symposium and a pleasant stay in Podčetrtek.